Reconstitution of human shelterin complexes reveals unexpected stoichiometry and dual pathways to enhance telomerase processivity - Ci Ji Lim (Nature Portfolio, 2017)
The human shelterin complex protects telomere ends from being recognized as damaged DNA sites and regulates telomere length in conjunction with telomerase. Here the authors establish the stoichiometries of human shelterin complexes of various compositions and show shelterin provides dual pathways to stimulate telomerase processivity.